Mitochondria‐mediated mitigatory role of curcumin in cisplatin‐induced nephrotoxicity. (13th February 2013) - Waseem, Mohammad; Kaushik, Pooja; Parvez, Suhel
<x xml:space="preserve">Abstract</x> Cisplatin (CP) is one of the most potent chemotherapeutic anti‐tumour drugs, and it has been implicated in renal toxicity. Oxidative stress has been proven to be involved in CP‐induced toxicity including nephrotoxicity. However, there is paucity of literature involving role of mitochondria in mediating CP‐induced renal toxicity, and its underlying mechanism remains unclear. Therefore, the present study was undertaken to examine the antioxidant potential of curcumin (CMN; a natural polyphenolic compound) against the mitochondrial toxicity of CP in kidneys of male rats. Acute toxicity was induced by a single intra‐peritoneal injection of CP (6 mg kg−1). We studied the ameliorative effect of CMN pre‐treatment (200 mg kg−1) on the toxicity of CP in rat kidney mitochondria. CP caused a significant elevation in the mitochondrial lipid peroxidation (LPO) levels and protein carbonyl (PC) content. Pre‐treatment of rat with CMN significantly replenished the mitochondrial LPO levels and PC content. It also restored the CP‐induced modulatory effects on altered enzymatic and non‐enzymatic antioxidants in kidney mitochondria. We hypothesize that the reno‐protective effects of CMN may be related to its predisposition to scavenge free radicals, and upregulate antioxidant machinery in kidney mitochondria. Copyright © 2013 John Wiley & Sons, Ltd.